Integrating Agricultural Risks Management Strategies in Selected EU Partner Countries: Syria, Tunisia, Turkey - Fabio G. Santeramo; Fabian Capitanio; Felice Adinolfi (Romanian Journal of European Affairs)
Dynamics and transitions in the agricultural sector of emerging countries are not yet well understood. A decade of major political and economic changes is challenging the Mediterranean Economies, affecting the primary sectors of transition economies which are largely influenced by recent trends. The resulting exposure of agriculture to risks has called great attention on risk management strategies and public intervention. We explore their role in three different economies with a view to a unified policy framework. The analysis is conducted through a field activity in Syria, Tunisia and Turkey that has allowed understanding the key issues. The experts’ opinions draw a clear picture of retrospect and prospects and stimulate a comparative analysis that widens the current knowledge of risk management in the EU Partner Countries.